2016
DOI: 10.1136/jclinpath-2015-203506
|View full text |Cite
|
Sign up to set email alerts
|

Two progressive pathways of microinvasive carcinoma: low-grade luminal pathway and high-grade HER2 pathway based on high tumour-infiltrating lymphocytes

Abstract: Our study revealed that microinvasive carcinoma has two progressive pathways; 'low-grade luminal pathway' and 'high-grade HER2 pathway'. HER2-positive cases showed the following unique characteristics: 'high-grade; comedo, high TIL and CD8+ TIL; healing; cluster-like invasion'. These results suggest that the cluster-like invasion might occur because of tumour immunity that leads to disruption of the duct and formation of microinvasive carcinoma in HER2-positive cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Some authors postulated associations between tumour infiltrating T-cell quantity and ER-as well as PR-negativity [40], which is in accordance with our results, while others did not [41]. Research into microinvasive breast cancer provided a hypothesis on immunogenicity of HER2-overexpressing tumours, which leads to the accumulation of cytotoxic T-cells, and, finally, to the rupture of the basement membrane [42]. Moreover, among luminal lesions, we noted that T-cells located at the invasive front of malignant lesions were the only subpopulation that differed significantly, with their highest density in luminal B/HER2+ lesions.…”
Section: Discussionsupporting
confidence: 91%
“…Some authors postulated associations between tumour infiltrating T-cell quantity and ER-as well as PR-negativity [40], which is in accordance with our results, while others did not [41]. Research into microinvasive breast cancer provided a hypothesis on immunogenicity of HER2-overexpressing tumours, which leads to the accumulation of cytotoxic T-cells, and, finally, to the rupture of the basement membrane [42]. Moreover, among luminal lesions, we noted that T-cells located at the invasive front of malignant lesions were the only subpopulation that differed significantly, with their highest density in luminal B/HER2+ lesions.…”
Section: Discussionsupporting
confidence: 91%
“…Supporting previous findings, our study has shown a significant association of high-TIL levels with triple-negative and HER2-positive subtypes of non-invasive breast cancer, which usually present high proliferation rates and high risk of invasion [ 16 , 21 , [35] , [36] , [37] ]. In previous studies, high-TIL levels have been observed in areas of microinvasive breast cancer, suggesting that more aggressive tumours may also be more immunogenic [ 12 , 36 , 38 , 39 ]. Additionally, the activation of the HER2 pathway seems to drive the tumoral stroma into a pro-immunogenic state, as HER2-positive tumours have a high frequency of CD8 + T cells and a low PD-L1 expression in their lymphocytic infiltrate [ 21 , 25 , [35] , [36] , [37] , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The role of the immune response in DCIS is an area of interest; however, the association between density of TILs and DCIS recurrence has not been well established due to a variety of controversial data. 12,13 Assessment of stromal TILs, as detailed by the International Immuno-Oncology Biomarker Working Group, did not demonstrate an association with DCIS recurrence. [14][15][16] A more recent methodology of TILs assessment, which looked at TILs touching DCIS ducts (touching-TILs), was found to be an independent prognostic variable for LR in DCIS.…”
Section: Introductionmentioning
confidence: 94%